Genetic variability and evolutionary analyses of the coat protein gene of Tomato mosaic virus - Rangel, Ezequiel A.; Alfaro-Fernández, Ana; Font-San-Ambrosio, Isabel; Luis-Arteaga, Marisol; Rubio, Luis (2017)
Tomato mosaic virus (ToMV), a member of the genus Tobamovirus, infects several ornamental and horticultural crops worldwide. In this study, the nucleotide sequences of the coat protein gene of worldwide ToMV isolates were analyzed to estimate the genetic structure and diversity of this virus and the involved evolutionary forces. The phylogenetic analysis showed three clades with high bootstrap support: Clade I contained three ToMV isolates from Brazil collected from pepper, Clade II comprised one Brazilian ToMV isolate from pepper, and Clade III was composed of ToMV isolates collected from different plant hosts (pepper, tomato, eggplant, lilac, camellia, dogwood, red spruce, etc.) and water (from melting ice, lakes and streams) from different countries: USA, Brazil, Korea, Germany, Spain, Denmark (Greenland), China, Taiwan, Malaysia, Iran, and Kazakhstan. With the exception of Brazil, nucleotide diversity within and between different geographic regions was very low, although statistical analyses suggested some gene flow between most of these regions. Our analyses also suggested a strong negative selection which could have contributed to the genetic stability of ToMV.